ASSESSMENT AND ANALYSIS OF STUDENTS' NEEDS FOR LEARNING VIRTUAL ROBOTICS BASED ON A SURVEY - Yadgarovna, Buronova Gulnora; Maruf qizi, Adizova Fotima (Journal of Higher Education and Academic Advancement, 2025)
Objective: The aim of this study is to assess and analyze students' needs regarding the learning of virtual robotics. As virtual technologies gain prominence in education, especially in robotics and engineering fields, understanding learners’ expectations and barriers becomes essential for designing effective curricula. Method: A structured survey was conducted among students at Bukhara State University to evaluate their familiarity, interest, and challenges related to virtual robotics education. The survey included quantitative Likert-scale questions and qualitative open-ended responses. Collected data were statistically analyzed, and key indicators were visualized through bar charts and pie graphs to enhance interpretability. Results: The analysis showed that over 65% of students expressed a high level of interest in virtual robotics, with accessibility and interactivity being the most appreciated features. Motivation levels were found to increase after exposure to simulation-based learning modules. Graphical data illustrated a clear shift in student engagement—from moderate to high—before and after the virtual course. However, gaps in digital literacy and access to devices were noted as limiting factors for some learners. Novelty: This study is among the first to combine statistical and graphical analysis to assess the virtual robotics readiness of Uzbek university students. The integration of visual data enhances the clarity and credibility of the findings. The results offer practical implications for educators seeking to implement virtual learning platforms in STEM disciplines within developing regions.